Synthetic Receptors with Micromolar Affinity for Chloride in Water. Issue 9 (24th January 2023) - Sudan, Sylvain; Chen, Damien W.; Berton, Cesare; Fadaei‐Tirani, Farzaneh; Severin, Kay
Abstract: A water‐soluble coordination cage was obtained by reaction of Pd(NO3 )2 with a 1, 3‐di(pyridin‐3‐yl)benzene ligand featuring a short PEG chain. The cavity of the metal‐organic cage contains one nitrate anion, which is readily replaced by chloride. The apparent association constant for chloride binding in buffered aqueous solution is K a =1.8(±0.1)×10 5  M −1 . This value is significantly higher than what has been reported for other macrocyclic chloride receptors. The heavier halides Br − and I − compete with binding or self‐assembly, but the receptor displays very good selectivity over common anions such as phosphate, acetate, carbonate, and sulfate. A further increase of the chloride binding affinity by a factor of 3 was achieved using a fluorinated dipyridyl ligand. Abstract : Water‐soluble coordination cages have been obtained by the reaction of Pd (NO3 )2 with 1, 3‐di(pyridin‐3‐yl)benzene ligands featuring a short PEG chain. The Pd‐based coordination cages are able to bind chloride in buffered aqueous solution with apparent binding constants exceeding 10 5  M −1 .